Mapping wheat potential: a GIS-based agro-land suitability analysis in Gujarat’s Bhal Region, Western India - Kumar, Ranjan; Ghosh, Subhankar; Patel, Gautam R.; Singh, Laishram Kanta; Mohanty, Amulya Kumar; Singha, Arun Kumar (Frontiers in Agronomy, 2025)
IntroductionAgro-land suitability evaluation is vital to determine the optimal use of agricultural land for specific crops, ensuring sustainable cultivation and maximizing yields.MethodsThis study focuses on assessing the suitability of land for wheat (Triticum L) cultivation in the Bhal region of Gujarat state, western India, a prominent agricultural area where fluctuating production levels have been attributed to sub-optimal crop selection. With wheat being a staple crop essential in meeting the demands of a growing population, systematic evaluation of the region’s land suitability is both timely and necessary. The analysis integrates a comprehensive range of parameters (17 in total), including land use/land cover, slope, soil texture, soil depth, maximum water-holding capacity, pH, Electrical Conductivity, Soil Organic Carbon, and the availability of essential macro-nutrients (N, P, K and S) and micro-nutrients (B, Cu, Fe, Mn and Zn). Using an advanced Multi-Criteria Decision Analysis (MCDA) methodology such as the Analytic Hierarchy Process (AHP) in a Geographic Information System (GIS) framework, a detailed land suitability map was developed for wheat cultivation.Results and discussionThe soils in the Bhal region are found to be deficient of Nitrogen (N), Manganese (Mn), Iron (Fe) and Zinc (Zn), which necessitates fertilizer application. The highest and lowest normalized weights were obtained for soil texture (0.291) and Zinc concentration (0.017), respectively. The findings revealed that 24.80% (1121.1 km2) of total area is categorized as ‘highly suitable’, 31.37% (1418.2 km2) as ‘moderately suitable’, 12.40% (560.6 km2) as ‘least suitable’, and remaining 31.43% (1420.9 km2) as ‘not suitable’ for wheat cultivation. Ahmedabad, Kheda and Surendranagar districts are ‘highly’ to ‘moderately’ suitable, while Anand district is ‘moderately’ suitable and Bhavnagar district is ‘least’ suitable for wheat cultivation.Concluding remarks and significanceThese results underscore the critical importance of soil fertility and crop-specific land assessment in guiding agricultural strategies. The present study provides valuable insights into agricultural land-use planning and crop management, offering a data-driven approach to enhance wheat productivity in the Bhal region. By addressing the challenges of crop selection and resource optimization, these findings contribute to ensuring food security and promoting sustainable agricultural practices in the region.